1991
DOI: 10.1161/01.cir.83.6.1923
|View full text |Cite
|
Sign up to set email alerts
|

Use of endovascular stents in congenital heart disease.

Abstract: BACKGROUND Balloon expandable intravascular stents have been used to support vessel walls in coronary and peripheral arteries in adults. The purpose of this study was to examine the efficacy and safety of these stents in the treatment of congenital heart disease. METHODS AND RESULTS Forty-five stents were placed in 30 patients, who were 0.2-30.2 years old (weight, 3.5-76 kg). Patients with areas of stenosis that were difficult to approach surgically wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
245
0
16

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 481 publications
(264 citation statements)
references
References 11 publications
3
245
0
16
Order By: Relevance
“…In the first series of BPAS stents, O'Laughlin et al [11] reported their results with 35 stents in 23 patients. They found that the peak pressure gradients decreased (51 +/-24 vs. 16 +/-13 mmHg; p<0.01) and the vessel diameter increased (5 +/-3 vs. 11 +/-4 mm; p<0.01).…”
Section: Immediate Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first series of BPAS stents, O'Laughlin et al [11] reported their results with 35 stents in 23 patients. They found that the peak pressure gradients decreased (51 +/-24 vs. 16 +/-13 mmHg; p<0.01) and the vessel diameter increased (5 +/-3 vs. 11 +/-4 mm; p<0.01).…”
Section: Immediate Resultsmentioning
confidence: 99%
“…Even with this technical improvement, success rate remained low, complication (ruptured pulmonary artery, hemoptysis, pulmonary edema, pulmonary artery aneurysm) rate was high, and recurrence rate was significant [43][44][45][46]. Consequently balloon expandable stents, first introduced by Palmaz et al [7], have been adopted for management of BPAS [11,16,17,[48][49][50] …”
Section: Branch Pulmonary Artery Stenosismentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26][27][28][29][30][31][32][33][34] Surgical approach has been tried in some instances, with variable results, depending on the technique used, anatomy, and timing of surgery. 24,26,31,34 In children, balloon angioplasty for PVS has been uniformly unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 In addition, endovascular stenting of the pulmonary veins in children has met with little clinical success. 25,[27][28][29][30] On the other hand, stent placement in the pulmonary veins after extrinsic compression in adults has yielded some clinical success. 23 The application of energy in the region of the pulmonary veins results in formation of organizing thrombus, necrotic myocardium, endovascular contraction, and proliferation of elastic lamina, in addition to intimal proliferation.…”
Section: Discussionmentioning
confidence: 99%